Correlates of distress in young people with cystic fibrosis: the role of self-efficacy and metacognitive beliefs. Issue 12 (29th November 2021) - Russell, Jeremy K.; Strodl, Esben; Kavanagh, David J.
Abstract: Objectives: While significantly elevated distress is repeatedly found amongst young people with cystic fibrosis, their determinants remain largely unknown. This study explored whether metacognitive beliefs and self-efficacy for emotion regulation were associated with anxiety and depression after control for physical functioning, age and gender. Design: Cross-sectional study using a 110-item online questionnaire. Methods: An online survey was undertaken by 147 young people with CF aged 10–18 from five countries. Associations of Hospital Anxiety and Depression Scale scores with gender, age, physical functioning, Metacognitive Beliefs Questionnaire for Children (MCQ-C) subscales and Self-Efficacy for Emotion Regulation (SE-ER) were examined using hierarchical multiple linear regressions. Results: Physical functioning, gender and age accounted for 31% of the variance in anxiety and 39% in depression. The MCQ-C and SE-ER added another 45% to the variance of anxiety and 32% to depression. At the final step of both analyses, physical functioning, SE-ER, MCQ-C Negative Meta-Worry and Superstition, Punishment & Responsibility contributed significantly. Older age was also significantly associated with depression. Conclusions: Self-efficacy for emotion regulation, concern about worrying and shame may be particularly important foci for interventions aimed at ameliorating anxiety and depression in young people with CF.